International Mission Centre (IMC) Universitas Kritsten Inonesia Paulus (UKIP) Makassar - P. Tongli P. Tongli (Universitas Islam Negeri Alauddin Makassar, 2015)
This writing depicts the future vision of religion in Indonesia. The methodology of the writing is using futurology analyzes to predict the condition of Indonesian religion in the future. Religion is one of the crucial problems in society and state, because it has role at living humanity. When religion to be harmony, the state and society harmony too. Meanwhile, the state is not harmony when religion or its followers are not harmony. The social involvement have to be undertaken the cooperation of religious as institution to promote justice, equal right, and prosperity. Therefore, the most important aspect that has to be promoted in Indonesia is not religious flash, but solidarity in promoting justice and prosperity.